Intravenous immunoglobulin transfusion in colostrum-deprived dairy calves. (March 2016) - Boccardo, A.; Belloli, A.; Biffani, S.; Locatelli, V.; Dall'Ara, P.; Filipe, J.; Restelli, I.; Proverbio, D.; Pravettoni, D.
Highlights: Plasma transfusion in colostrum-deprived dairy calves was evaluated. IgG doses of 62.7 ± 3.1 g given IV provided adequate serum IgG concentrations in colostrum-deprived calves (>10 g/L). Colostrum fed calves had significantly lower morbidity and mortality rates compared to the transfused calves. Plasma transfusion is ineffective to provide a complete protection against neonatal disease in colostrum-deprived calves. Future trials should assess the impact of high doses of IgG in terms of outcome in naturally sick calves with FPT. Abstract: Immunoglobulin transfusion is employed in the management of the failure of passive transfer (FPT). The aim of this study was to investigate the dose of immunoglobulin G (IgG) needed to reach a protective concentration (>10 g/L) in colostrum-deprived dairy calves. Twenty-eight Holstein Friesian newborn male calves were randomly assigned to either a control group (CG) or a treatment group (PG). Calves in the CG received 4 L of high quality colostrum within 12 h of birth. Calves in the PG received 62.7 ± 3.1 g of IgG IV in 2.6 ± 0.3 L of plasma within 6 h after birth. Serum immunoglobulin G (sIgG) and serum total protein (sTP) concentrations were assayed before and after (24 h, 72 h and 1 week after birth) plasma transfusion or colostrum ingestion. Serum (s) IgG and sTP concentrations increased in both groups throughout the period of observation. Mean sIgG and sTP concentrations after colostrum ingestion or plasma transfusion were higher in the CG than in the PG ( P < 0.01). Nine treated calves developed diarrhoea during the study and four were humanely euthanased due to progressive clinical deterioration. None of the calves in the CG showed signs of disease or died during the study. The dose of IgG used in this trial effectively provided an adequate sIgG concentration in colostrum-deprived calves (>10 g/L). Calves in the CG had significantly lower morbidity and mortality rates compared to those in the PG, suggesting that plasma transfusion alone is ineffective in providing complete protection against neonatal disease.